Association between several persistent organic pollutants and thyroid hormone levels in serum among the pregnant women of Korea - Kim, Sunmi; Park, Jeongim; Kim, Hai-Joong; Lee, Jeong Jae; Choi, Gyuyeon; Choi, Sooran; Kim, Sungjoo; Kim, Su Young; Moon, Hyo-Bang; Kim, Sungkyoon; Choi, Kyungho (Environment international, 2013)
Persistent organic pollutants such as polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), and organochlorine pesticides (OCPs) are of global concern because of their widespread contamination and adverse health effects. Potential endocrine disruption, especially of thyroid status by PCBs has been repeatedly suggested in both experimental and epidemiological studies. However the associations with PBDEs or OCPs have been arguable especially in human populations. We investigated the associations between major groups of POPs and thyroid hormone balances among pregnant women. One hundred five pregnant women at delivery were recruited from four cities of Korea in 2011 and were investigated. Blood samples were collected within a day before delivery. Serum was then analyzed for 19 PCBs, 19 PBDEs, and 19 OCPs, along with five thyroid hormones (free and total T3 and T4, and TSH). Several PCBs such as PCB28, 52, and 118 showed negative associations with T3 or T4. BDE47 and total PBDEs showed significant associations with T3 or T4. For OCPs, dichlorodiphenyltrichloroethanes (DDTs) and hexachlorobenzene (HCB) were generally associated with reduction of T3 or T4. The thyroid hormone levels of all subjects were within the reference range, however exposure to several target POPs were clearly related with potential for disrupting thyroid hormone balance among pregnant women, at the current level of exposure. Although subtle, the changes in thyroid hormones should be seen with caution because even minor changes within pregnant women may have significant consequences especially on sensitive population like fetus. •Associations between POPs and thyroid hormone levels were examined in pregnant women.•Several PCBs and OCPs are significantly associated with T3 or T4 levels.•PBDEs showed thyroid disrupting potential, but the directions were inconsistent.•Implications of POPs exposure on fetus during gestation deserve further investigation.